Necrostatin-1 Alleviates Lung Ischemia-Reperfusion Injury via Inhibiting Necroptosis and Apoptosis of Lung Epithelial Cells - Lingjun Dong; Fuxiang Liang; Zhiling Lou; Yangfan Li; Jinsheng Li; Yaling Chen; Jingjing Ding; Bin Jiang; Chuanqiang Wu; Huan Yu; Yafei Liu; Weiping Zhang; et al. (Cells, 2022)
Lung ischemia-reperfusion injury (LIRI) is associated with many diseases, including primary graft dysfunction after lung transplantation, and has no specific and effective therapies. Necroptosis contributes to the pathogenesis of ischemia-reperfusion injury. Necrostatin-1 (Nec-1), the necroptosis inhibitor targeting RIPK1, has been reported to alleviate ischemia-reperfusion injury in various organs. However, the underlying mechanism of Nec-1 in LIRI remains unclear. In this paper, an in vivo LIRI model was built up by left lung hilar clamping in mice, and an in vitro cold ischemia-reperfusion (CI/R) model using BEAS-2B cells was applied to mimic the lung transplantation setting. We found Nec-1 significantly alleviated ischemia-reperfusion-induced lung injury, cytokine releasing, and necroptosis of epithelial cells in mouse lungs. In vitro, Nec-1 also mitigated CI/R-induced cell death and inflammatory responses in BEAS-2B cells, and these protective effects were achieved by simultaneously inhibiting the formation of necrosome and RIPK1-dependent apoptosis. However, Nec-1 decreased the necrosome number but increased the apoptosis level in lung tissues after ischemia reperfusion. We further clarified that Nec-1 could also attenuate lung injury by promoting neutrophil apoptosis from flow cytometry. In conclusion, Nec-1 alleviated lung ischemia-reperfusion injury by inhibiting necroptosis and apoptosis of epithelial cells and promoting the apoptosis of neutrophils. Thus, Nec-1 could be a promising medication against primary graft dysfunction after lung transplantation.